Paradoxical impact of socioeconomic factors on outcome of atrial fibrillation in Europe: trends in incidence and mortality from atrial fibrillation - Al-Khayatt, Becker M; Salciccioli, Justin D; Marshall, Dominic C; Krahn, Andrew D; Shalhoub, Joseph; Sikkel, Markus B (European heart journal, 2021)
The aim of this study was to understand the changing trends in atrial fibrillation (AF) incidence and mortality across Europe from 1990 to 2017, and how socioeconomic factors and sex differences play a role. We performed a temporal analysis of data from the 2017 Global Burden of Disease Database for 20 countries across Europe using Joinpoint regression analysis. Age-adjusted incidence, mortality, and mortality-to-incidence ratios (MIRs) to approximate case fatality rate are presented. Incidence and mortality trends were heterogenous throughout Europe, with Austria, Denmark, and Sweden experiencing peaks in incidence in the middle of the study period. Mortality rates were higher in wealthier countries with the highest being Sweden for both men and women (8.83 and 8.88 per 100 000, respectively) in 2017. MIRs were higher in women in all countries studied, with the disparity increasing the most over time in Germany (43.6% higher in women vs. men in 1990 to 74.5% higher in women in 2017). AF incidence and mortality across Europe did not show a general trend, but unique patterns for some nations were observed. Higher mortality rates were observed in wealthier countries, potentially secondary to a survivor effect where patients survive long enough to suffer from AF and its complications. Outcomes for women with AF were worse than men, represented by higher MIRs. This suggests that there is widespread healthcare inequality between the sexes across Europe, or that there are biological differences between them in terms of their risk of adverse outcomes from AF.